The impact of electronic banking marketing on the quality of banking services - a case study of the Tigris and Furat Bank for Development and Investment - شيرين بدري توفيق البارودي, (Iraqi Journal for Administrative Sciences, 2025)
Revolutionized information & communication many changes in the areas of business including the business environment of banks & especially in services, which saw the developments & financial innovations & banking in response to the rapid developments witnessed by this environment & expansion in the use of channels of Electronic Banking Marketing banking products as banks began to exercise financial services industry with quality & strategic value To retain customers & increase the chances of selling banking services & enhance reputation, reduce costs, increase profits, market share & improve the performance of banking, which in turn reflected positively on the quality of banking service. This study is of great importance to commercial banks Iraqi (government – privet ) due to the importance of marketing Electronic banking to provide quality service with the necessity of activating the activities of marketing banking and the trend towards the use of electronic channels & to harness the mechanisms & especially the Internet, both in payment & settlement of electronic or completion of Banking operations down to the marketing of banking services to reach to achieve customer satisfaction & the satisfaction of desires& upgrading the quality of banking services in the Iraqi banking sector.